Effect of adaptive management practices on carbon footprint of sugarcane in the agroecological landscape of Bihar, India - Kudi, Babita; Meena, Sunita Kumari; Kumar, Ajeet; Meena, Vijay Singh; Laik, Ranjan (Frontiers in Sustainable Food Systems, 2025)
This study evaluates adaptive management in sugarcane cultivation through varied input strategies and legume integration. A total of 380 soil samples were collected across blocks at two depths (0–15 and 15–30 cm). Results showed that at 0–15 cm, oxidizable soil organic carbon (SOC) ranged from 3.19 to 8.01 g kg−1, and at 15–30 cm, it ranged from 2.50 to 6.90 g kg−1. The C indices showed a decreasing trend with depth. Total organic carbon (TOC) varied from 5.68 to 11.4 g kg−1 at 0–15 cm and from 3.85 to 11.4 g kg−1 at 15–30 cm. Permanganate-oxidizable carbon (KMnO4-C) ranged from 145 to 382 mg kg−1 at 0–15 cm and from 122 to 356 mg kg−1 at 15–30 cm. Carbon stock ranged from 12.6 to 25.9 Mg ha−1 at 0–15 cm, and from 10.2 to 24.5 Mg ha−1 at 15–30 cm. The active carbon pool decreased by 17.59%, the passive pool changed negligibly (0.22%) with depth; lability and recalcitrance indices showed carbon stability differences. Study offers key farm-level insights on carbon footprints and adaptive sugarcane management.